Characteristics of the Morphology and Hatchability of Egg White Nest Swiftlets (Aerodramus fuciphagus) under Artificial Incubation Conditions - Wenas, Karl; Hartandi, Nugroho; Arif, Ani Atul; Andri, Faizal; Minarti, Sri; Isnaini, Nurul (Faculty of Animal Science, Universitas Brawijaya, 2025)
The increasing demand for edible bird nests (Aerodramus fuciphagus) has raised concerns regarding the sustainability of swiftlet populations. Artificial incubation is a potential solution to mitigate the impact of nest harvesting on wild populations. This study aimed to examine the morphological characteristics of swiftlet eggs from Buntok, Central Kalimantan, and their hatchability under controlled incubation. The 240 fertile eggs from a total of 400 eggs were incubated at 33–34.5°C with 70–80% humidity, and hatchability rates were assessed. The results indicated that swiftlet eggs had an average weight of 1.74 ± 0.151 g, length of 2.01 ± 0.090 cm, and width of 1.29 ± 0.038 cm. Descriptive analyses (means ± standard deviations) were performed for egg morphology parameters. Correlation analysis (Pearson’s correlation coefficient) was conducted to examine the relationships between egg characteristics and hatchability. Statistical analysis revealed a weak but significant correlation between egg weight and hatchability (p = 0.041), whereas egg length and width had no significant effect. Oval-shaped eggs had a slightly higher hatch success rate (62.5%) than elongated eggs did (60.0%). Hatchability was significantly influenced by incubation conditions, with stable temperature and humidity levels increasing embryonic survival. Regular egg turning (six times per day) improved hatch success, which aligns with findings in other avian species. These results contribute to swiftlet conservation and sustainable farming by optimizing artificial incubation protocols.